Hello,Originally Posted byRocher

you have to rearrange your equations, so that the x is on one side and the constants on the other side of the equation. The final step ist to divide both sides of the equation by the coefficient of x:

(Remark: This sign "|" means: Do onboth sidesof the equation what follows directly this sign. I'll do the final step only with the first problem. With the following problems your at your own.)

a) 8x-11=3x+27 | -3x + 11 you'll get: 5x = 38 | /5 -----> x = 38/5

b) -5x=26-7x |+7x ----> 2x = 26 ----> x = 13

c) -5x+2=6x-1 |-6x -2 ----> -11x = -3 ---> x = 3/11

d) -4x-5=3x+2 | -3x + 5 ----> -7x = 7 ----> x = -1

e) -5x+3=15-x | +x - 3 ----> -4x = 12 ----> x = -3

f)

g) -13x+11=24-7x | +7x - 11 ----> -6x = 13 ----> x = -13/6

h) -6x+7-19=7x-8-3x <==> -6x - 12 = 4x-8 | -4x+12 ---> -10x = 4 ---> x = -2/5

i) 4x+5x+21=24-3x <==> 9x + 21 = -3x + 24 | +3x-21 ----> 12x = 3 ----> x = 1/4

I hope that I prevented your early and unexpected death.

Greetings and welcome to life!

EB